The Small Molecule PPARγ Agonist GL516 Induces Feeding-Stimulatory Effects in Hypothalamus Cells Hypo-E22 and Isolated Hypothalami - Annalisa Chiavaroli; Viviana di Giacomo; Barbara De Filippis; Amelia Cataldi; Claudio Ferrante; Letizia Giampietro (Molecules, 2022)
PPARγ agonists are implicated in the regulation of diabetes and metabolic syndrome and have therapeutic potential in brain disorders. PPARγ modulates appetite through its central effects, especially on the hypothalamic arcuate nucleus (ARC). Previous studies demonstrated that the small molecule GL516 is a PPARγ agonist able to reduce oxidative stress and apoptosis with a potential neuroprotective role. Herein, we investigated the effects of GL516, in vitro and ex vivo, on the levels of hypothalamic dopamine (DA) and serotonin (5-HT). The gene expressions of neuropeptide Y, CART, AgRP, and POMC, which play master roles in the neuroendocrine regulation of feeding behavior and energy balance, were also evaluated. HypoE22 cells were treated with H2O2 (300 μM) for 2 h e 30’ and with different concentrations of GL516 (1 nM-100 µM). The cell viability was evaluated after 24 and 48 h of culturing using the MTT test. DA and 5-HT levels in the HypoE22 cell supernatants were analyzed through HPLC; an ex vivo study on isolated hypothalamic specimens challenged with scalar concentrations of GL516 (1–100 µM) and with pioglitazone (10 µM) was carried out. The gene expressions of CART, NPY, AgRP, and POMC were also determined by a quantitative real-time PCR. The results obtained showed that GL516 was able to reduce DA and 5-HT turnover; moreover, it was effective in stimulating NPY and AgRP gene expressions with a concomitant reduction in CART and POMC gene expressions. These results highlight the capability of GL516 to modulate neuropeptide pathways deeply involved in appetite control suggesting an orexigenic effect. These findings emphasize the potential use of GL516 as a promising candidate for therapeutical applications in neurodegenerative diseases associated with the reduction in food intake and stimulation of catabolic pathways.